Senior High School Students’ Experiences in Using Podcast to Learn English Speaking - Kusuma Dewi, Aprilia Ayu (Universitas Negeri Surabaya, 2023)
In the fast-developing 21st century, various innovative media have been introduced in learning English speaking; one of the popular products of technology created to support learning English speaking is Podcast. Currently, Podcast has a variety of content that can assist and support secondary-level students in learning English speaking. Some previous studies found that Podcasts can improve students' speaking skills, but they still did not show how students make the most of Podcasts for learning to speak English. Therefore, this study aimed to find out students' experiences using Podcasts and how students make the most of Podcasts for learning English speaking. This study was a survey study. This research was carried out by surveying 15 eleventh graders in the Sidoarjo and Surabaya area, specifically, students who have experience using Podcasts to learn English speaking more than once. To collect the data, the researcher used open-ended questionnaires distributed to participants in Google Forms that spread through the Social Media. The results showed that podcasts can make it easier for students to access authentic material from native speakers since it provides kinds of Podcasts with various popular Podcast theme content. Podcasts can assist students in focusing on their aspects of speaking, such as grammar, fluency, vocabulary, pronunciation, etc. Students used the Podcast in the common ways they did while learning, such as searching the Podcast on an online platform, listening and watching, taking notes, realizing, practicing. It can be concluded that Podcast was a beneficial learning media resource for learn English speaking.